Einstein: determinismo o libre albedrío. Reflexiones en torno a la ética (2005)
The Einstein’s Worldview with its aspects of realism, reductionism and determinism is presented. The last two characteristics lead him to deny a real, objective character to freewill that would be just an appearance. His theses about Ethics are then analyzed and finally some critical commentaries about his ideas are presented.